ANALISIS UPACARA “PUKUL SAPU” di NEGERI MORELLA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Abdul Manaf Tubaka (IAIN Ambon, 2019)
ABSTRAK This study aims to reveal the meaning of the tradition of Pukul Sapu ceremony in Morella which is held annually on the 7th of syawal or seven days after Eid al-Fitr. The method used in this study is the verstehen method with a qualitative approach. Research instrument is the researcher itself with interview method, participatory observation to understand the context of an event. The results of the study illustrate that the tradition of Pukul Sapu in Morella with the symbol attributes used has a variety of meanings for the people of Morella. Therefore, these traditions can drive people's behavior in their daily life. In addition, Pukul Sapu tradition becomes a construction of a unique cultural identity and gives influence to the social integration of the Morella people. The existence of Pukul Sapu Ceremony becomes a marker of historical awareness for people of Morella and has functional value for people of Maluku in general. Keywords: Tradition, Pukul Sapu, and Symbol Meaning.